Investigating the Influence of Blanching on the Drying Characteristics and Sorption Isotherm of Cherry Tomatoes (Lycopersicum Esculentum Var. Cerasiforme) - Selpiah, Selpiah; Salengke, Salengke; Salim, Iqbal; Sapsal, Muhammad Tahir (Salaga Journal, 2023)
Cherry tomatoes have a fairly short shelf life due to the influence of high water content and enzymes present in the fruit. Blanching is used to inactivate enzymes that can damage the quality of tomatoes. This research was conducted with the aim of studying the effect of blanching on the drying rate and sorption isotherm of cherry tomatoes. Blanching was done at 60 °C, 70 °C, 80 °C. After blanching, the samples were dried at 60 °C. After drying the samples were stored in a desiccator containing a solution for 24 days using NaOH, MgCl2, K2CO3, NaNO2, and NaCl. The results obtained in the blanching process have a lighter color than before blanching based on the L.a.b value. The moisture content of the sample during drying can be seen from the MR and drying rate which have almost the same value, only the time to reach 12% moisture content is different. The sorption isotherm process in the control treatment, blanching with temperatures of 60 °C, 70 °C and 80 °C with time (15, 30 and 45 minutes) experiences two processes, namely desorption (water release) at low RH and absorption (water binding) which occurs at high RH. The conclusion obtained is that the sorption process only occurs at 60 °C blanching with a time of 15 minutes at low RH and other treatments experience desorption.